(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2001)
Electra and her brother Orestes kill their mother Clytemnestra Did average the death of their father Agamemnon. Thus the order of the city is re-established and Orestes returns to reign in his father’s place. Elektra, however, is condemned to Madness and roaming the streets of the city. in her poem, “ Electra en la niebla”, Gabriela Mister tries to understand the world of the mythical character. This study attempts to make a connection between traditional reading of Sophoclean tragedy and the new interpretation given by the lyric voice in the poem, which uses Electra to expose the space limitation imposed on women. It also systematically deconstructs the varied interpretations of the character of Electra, comparing them to the way in which Gabriela Mistral re-construct her Electra.